2003
DOI: 10.1007/s000490300006
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and metabolism of [ 14 C]rinderine and [ 14 C]retronecine in leaf-beetles of the genus Platyphora and alkaloid accumulation in the exocrine defensive secretions

Abstract: Summary. Sequestration and processing of pyrrolizidine alkaloids (PAs) by leaf beetles of the genus Platyphora were investigated. Tracer experiments with labeled alkaloids were performed with P. eucosma feeding on Koanophyllon panamense (Asteraceae, tribe Eupatorieae). P. eucosma catalyzes the same reactions previously demonstrated for P. boucardi specialized to Prestonia portobellensis (Apocynaceae): (i) epimerization of rinderine to intermedine; (ii) esterification of retronecine yielding insect-specific PAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…To ensure that metabolites in the insects are indeed sequestered from the host plants, feeding experiments with labelled compounds generally give the clearest evidence (e.g. Scudder and Meredith 1982b;Nahrstedt and Davis 1986;Lindigkeit et al 1997;Ehmke et al 1999;Narberhaus et al 2003;Pasteels et al 2003a).…”
Section: Discussionmentioning
confidence: 99%
“…To ensure that metabolites in the insects are indeed sequestered from the host plants, feeding experiments with labelled compounds generally give the clearest evidence (e.g. Scudder and Meredith 1982b;Nahrstedt and Davis 1986;Lindigkeit et al 1997;Ehmke et al 1999;Narberhaus et al 2003;Pasteels et al 2003a).…”
Section: Discussionmentioning
confidence: 99%
“…PAs entering the hemolymph as tertiary alkaloid are detoxified by efficient glucosylation . So far, only species of leaf beetles from the neotropical genus Platyphora are known to store PAs exclusively as tertiary alkaloids , Pasteels et al 2003a. Tracer studies with P. boucardi revealed that this beetle seems to efficiently transport the poisonous tertiary PAs directly into its defensive glands.…”
Section: Discussionmentioning
confidence: 99%
“…While certain compounds, such as amino acid and nicotinamide nucleotide derivatives, show no evident taxonomic association within the Chrysomelidae, three main classes of secretions appear to be specific to subtribes of beetles (see Pasteels et al 2003a). The Chrysomelina are characterized by isoxazolinone glucosides esterified by one or more nitropropanoic acid moieties, the Chrysolinina, by steroids (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…PAs are sequestered from plants or derived from plant PAs or necine bases Pasteels et al 2003b). Triterpene saponins are derived from β-amyrin (unpublished results), a common constituent of leaf waxes.…”
Section: Introductionmentioning
confidence: 99%